The effect of activated charcoal and bentonite toothpaste on extrinsic tooth discoloration - Melaniwati, Melaniwati; Putri, Naura Belinda; Ratnasari, Dina; Dwisaptarini, Ade Prijanti (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Tooth discoloration is categorized into intrinsic and extrinsic types, with the latter caused by external staining agents such as pigmented beverages (e.g., black tea). Whitening toothpastes are commonly used to address extrinsic discoloration, though chemical-based formulations may lead to side effects. Consequently, natural alternatives, including activated charcoal and bentonite, are gaining attention as whitening agents. This study aimed to evaluate the effects of activated charcoal and bentonite toothpaste on extrinsic tooth discoloration. A control group pretest-posttest design was employed, involving 48 premolar teeth divided into four groups. Samples were stained by immersion in a black tea solution (400 mL water, 4 tea bags) for 4 hours daily over 13 days, simulating 7 months of tea consumption. Color measurements were conducted using a spectrophotometer before and after brushing. Brushing was carried out using an electric toothbrush with 0.5 g of toothpaste and 1 mL of distilled water for 2 minutes, twice daily, over 10 days. Repeated ANOVA analysis revealed significant differences in ΔE, ΔL, and ΔC values (p < 0.05). Activated charcoal toothpaste produced a marked lightening effect and increased color intensity, although no change was observed at the cervical region of the teeth. These findings suggest that activated charcoal may serve as an effective natural agent for managing extrinsic discoloration while further research is needed to clarify its long-term effects and clinical applications.